Histochemical and Certain Immuno-histochemical Studies on the Sheep Liver during Prenatal and Postnatal Development - Choudhury, A.R. (Indian Journal of Veterinary Anatomy, 2020)
The present study was undertaken to investigate the immuno-histochemical changes in the liver during prenatal and postnatal development. The prenatal embryo/fetuses were divided in to three groups viz. Group1 (Early prenatal period, 0-50 days of gestation), Group 2 (Mid prenatal period, 51-100 days of gestation), Group 3 (Late prenatal period, 101 days-till parturition) and Group 4 included postnatal sheep below one year of age. The histochemical observation revealed moderate neutral mucopoly-saccharide content in both capsular andparenchymal cells at 42 days of gestation (3.20 cm CAL) and as the age of the fetus advanced the neutral mucopolysaccharides content increased. Other histochemical moieties such as acidic mucopolysaccharides, proteins gradually increased from moderate to strong with the increase in gestational age suggesting increased metabolic activity. Prenatal sheep liver during Group1 stage contained intercellular phospholipids droplets and as the age of the fetus advanced droplets started appearing intracellularly also. Kupffer cells of prenatal and postnatal sheep were numerous in the periportal than the pericentral areas and number in fetal and postnatal liver showed a progressive increase with age.